2023
DOI: 10.1039/d3ra01888a
|View full text |Cite
|
Sign up to set email alerts
|

Current status ofN-,O-,S-heterocycles as potential alkaline phosphatase inhibitors: a medicinal chemistry overview

Abstract: Heterocycles, powerful inhibitors of alkaline phosphatase (AP), are compounds that hinder an enzyme crucial for vital physiological functions including bone metabolism, cell growth, and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 176 publications
0
4
0
Order By: Relevance
“…Their roles are linked to several diseases like cancer, Alzheimer's disease and osteoporosis. 53,54 The catalytic site of alkaline phosphatases (APs) typically contains three metal ions, two Zn 2+ ions and one Mg 2+ ion. There are two main types of APs based on their tissue distribution in humans: i) tissue non-specific AP (TNAP) and ii) placental AP (PLAP).…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Their roles are linked to several diseases like cancer, Alzheimer's disease and osteoporosis. 53,54 The catalytic site of alkaline phosphatases (APs) typically contains three metal ions, two Zn 2+ ions and one Mg 2+ ion. There are two main types of APs based on their tissue distribution in humans: i) tissue non-specific AP (TNAP) and ii) placental AP (PLAP).…”
Section: Othersmentioning
confidence: 99%
“…Many heterocyclic compounds have been found to be potent inhibitors of APs. 54,57,58 Bhatti et al synthesized a series of sultams shown in Fig. 25 (compounds 25a–n ) and evaluated their potential as inhibitors of bovine tissue non-specific alkaline phosphatase (bTNAP) and intestinal alkaline phosphatase (bIAP).…”
Section: Othersmentioning
confidence: 99%
“…1,2 The abnormal level of ALP has been linked to diseases such as cancer and osteoporosis. 3,4 Consequently, the ALP assay has become a focal point in clinical diagnosis. Nowadays, various types of sensors have been developed using different signal models, such as absorbance, fluorescence, electrochemistry, and magnetic relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is ubiquitously distributed in the human body and involved in various physiological processes like bone metabolism, cell growth, and differentiation. , The abnormal level of ALP has been linked to diseases such as cancer and osteoporosis. , Consequently, the ALP assay has become a focal point in clinical diagnosis. Nowadays, various types of sensors have been developed using different signal models, such as absorbance, fluorescence, electrochemistry, and magnetic relaxation. , Among these, colorimetric sensors stand out due to their ease of preparation, user convenience, and potential for visual detection. , …”
Section: Introductionmentioning
confidence: 99%